Malayalam Question Answering System. (2016) - Seena, I.T.; Sini, G.M.; Binu, R.
Abstract: Question answering system, an important part in natural language processing aims at automatically finding concise answers to arbitrary questions phrased in natural language. The goal is difficult while considering the agglutinative nature of south Indian language Malayalam. Studies indicating that the usage of Malayalam documents on the web is increasing. In this paper we aim at retrieving factoid answers for the questions in Malayalam from a given set of Malayalam documents under a closed domain. TnT tagger is used to train the corpus of words inorder to find the precise factoid answers.